Textbook on international law - Dixon, Martin (Oxford University Press, 2013)
The seventh edition of Textbook on International Law offers students new to the subject a concise and focused introduction to the essential topics of an international law course. Dixon brings the subject to life with the use of topical examples to illustrate key concepts.